The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae - Burckhardt, Daniel; Queiroz, Dalva L. (Zootaxa, 2017)
The Neotropical psyllid genus Tainarys Brèthes, 1920 is revised to include 14 extant and one fossil species from Dominican amber. Eight species are described as new, viz. Tainarys aroeira sp. nov., T. atra sp. nov., T. hapla sp. nov., T. myracrodrui sp. nov., T. nigricornis sp. nov., T. didyma sp. nov. and T. orientalis sp. nov. from Brazil, the last two also from Uruguay, as well as T. lozadai sp. nov. from Peru. The fifth instar immatures are described for nine species. †Vicinilura Klimaszewski, 1996, erected for the fossil †V. reposta Klimaszewski, 1996 and previously synonymised with Leurolophus Tuthill, 1942, is synonymised here (syn. nov.) with Tainarys and †V. reposta is transferred to become †Tainarys reposta (Klimaszewski), comb. nov. The descriptions are supplemented by illustrations and keys for the identification of adults and immatures. Phylogenetic relationships between species are investigated with a cladistic analysis using 22 adult and six immature morphological characters. The analysis resulted in a single most parsimonious, fully resolved tree. The fossil species is nested within the genus rather than being the sister taxon of the remainder of species. The extant species are restricted to the subtropical and temperate parts of South America. Three pairs of sister clades display an east‒west South American and one a midwest‒southern Brazilian geographical vicariance. Host plants are confirmed for nine and likely for another four species. They are Astronium, Haplorhus, Myracrodruon, Schinopsis and Schinus (Anacardiaceae). All Tainarys species appear to be oligophagous inducing irregular leaf curls on their hosts.